TORITATEJOSHI BAKARI SEBAGAI PARTIKEL LIMITATIF DAN PADANANANNYA DI DALAM BAHASA INDONESIA - Felicia Aprilani (IZUMI, 2015)
In Japanese toritatejoshi Bakari is a particle that shows the meaning of limitation by way of highlight an element in the sentence and shows that there is only one element of the sole, while the other elements similar omitted. Meanwhile in a Indonesian Toritatejoshi Bakari has lexical meaning 'just' and 'only'. Matching of toritatejoshi Bakari in a Indonesian language included in limitedly adverb is an adverb that describes the meaning associated with the limitation. The problem in a this paper are (1) What is the structure of a sentence that uses toritatejoshi Bakari as limiting particle in a Japanese sentences and their counterparts in a Indonesian? (2) What is the meaning of a sentence that uses toritatejoshi Bakari as limiting particle in a Japanese sentences and their counterparts in a Indonesian? (3) What is the scope of toritatejoshi Bakari as limiting particle in a Japanese sentences and their counterparts in a Indonesian?. Based on the analysis conducted, it is known appropriation of both languages. In practical terms this study are expected to be useful for foreign language speakers of Japanese in the understanding toritatejoshi fueled as barrier particles so as to assist in the Japanese language proficiency both orally and in writing and helps understanding in Indonesian